2013
DOI: 10.1667/rr3239.1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Radiosensitivity Analyzed by FISH in Lymphocytes of Prostate Cancer Patients and Healthy Donors

Abstract: It is known that about 5-10% of cancer patients show severe clinical side effects during and after radiotherapy due to enhanced sensitivity to ionizing radiation. Identification of those radiosensitive individuals by a reliable in vitro assay before onset of treatment would have a great impact on successful radiotherapy. We compared the radiosensitivity of the chromosomes 2, 11 and 17 in prostate cancer patients with and without severe side effects after radiotherapy and in age-matched healthy donors. Each coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…Even though an age effect was not evident among adults, interindividual variation due to intrinsic genetic factors may still influence radiation responses (18). A recent report by Schmitz et al (19) indicates that patients with and without radiotherapy-induced side effects cannot be distinguished from healthy subjects, these results argue against the existence of substantial inter-individual sensitivity of adults to ionizing radiation. Of further interest is the observation by Ohtaki et al (20) that human fetuses exposed to ionizing radiation from the atomic bombs do not have elevated frequencies of translocations in their peripheral blood lymphocytes, except for a small increase at doses below 0.1 Sv.…”
Section: Discussionmentioning
confidence: 97%
“…Even though an age effect was not evident among adults, interindividual variation due to intrinsic genetic factors may still influence radiation responses (18). A recent report by Schmitz et al (19) indicates that patients with and without radiotherapy-induced side effects cannot be distinguished from healthy subjects, these results argue against the existence of substantial inter-individual sensitivity of adults to ionizing radiation. Of further interest is the observation by Ohtaki et al (20) that human fetuses exposed to ionizing radiation from the atomic bombs do not have elevated frequencies of translocations in their peripheral blood lymphocytes, except for a small increase at doses below 0.1 Sv.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted, that in two studies using the MN test [77,87] and in one using the ChA test [75], which did not detect a predictive value of cytogenetics, the irradiated lymphocytes were cultured longer than is normally done according to biodosimetry standards [39] and without an indicator for cell cycle (such as BrdU for ChAs), even though the doses used for ex vivo irradiation (2-3.5 Gy) were not high enough to cause a significant mitotic delay. The absence of correlation between cytogenetic and clinical radiosensitivity in these reports can, therefore, be partially attributed to aberration-free cells surviving into 2nd divisions while damaged cells would more likely be eliminated in the 1st division.…”
Section: The Role Of Dose and Dose Rate Of Ex Vivo Exposuresmentioning
confidence: 99%
“…Until now, there have not been many studies on the correlation between Arg72Pro and radiosensitivity. Comprehensive studies about the association between TP53 Arg72Pro polymorphism and radiosensitivity were already performed by Alsbeih et al [8,28]. In 2007 Alsbeih et al observed an increase of survival in fibroblast cells using clonogenic assay after exposed to single radiation dose ranging from 0 to 4 Gy in cells containing Proline coding allele in TP53 (Arg72Pro) gene.…”
Section: Association Between Tp53 Arg72pro Polymorphism and Radiosensmentioning
confidence: 99%
“…Until now the chromosomal aberration assay is the most commonly used assay to predict individual radiosensitivity. In brief, lymphocytes are irradiated in vitro in the G 0 phase and then stimulated to proceed in the cell cycle [8]. Another technique also commonly used for the assessment of individual radiosensitivity is G 2 micronucleus (MN) assay.…”
Section: Introduction mentioning
confidence: 99%